Analysis of Students’ Chemical Bonding Misconception with A Four-Tier Diagnostic Test - Rosyidah Syafaatur Rohmah; Nikmatin Sholichah; Yunilia Nur Pratiwi; Rizki Nur Analita (Jurnal Tadris Kimiya, 2022)
Students had difficulty understanding the chemical bonding concept because of its complex and abstract nature. This difficulty could lead to chemical bonding misconceptions. This study aimed to investigate basic chemistry students' misconceptions of chemical bonding. This study used a descriptive research design with a four-tier diagnostic test. The research’s subjects were basic chemistry students. Chemical Bonding Diagnostic Tool (CBDT) was used as an instrument to determine students' misconceptions. The results showed that students who had misconceptions about ionic, covalent, and coordinate covalent bonding were 48.90%, 53.00%, and 37.50%, respectively. The misconception in this course is that students need to learn about ionic bonds formed by electrostatic forces between cations and anions. As a result, students cannot determine the difference in electronegativity values in ionic and covalent bonds and the number of valence electrons of each atom in a chemical bonding. Therefore, the misconception is in the moderate category.